Acoustic homogeneity in the piranha Serrasalmus maculatus. Issue 5 (19th January 2021) - Raick, Xavier; Rountree, Rodney; Kurchevski, Gregório; Juanes, Francis; Huby, Alessia; Godinho, Alexandre L.; Parmentier, Éric
Abstract: Different studies suggest some social calls could be used in fish identification if their specificity is unambiguously assessed. Sounds of different populations of piranhas Serrasalmus maculatus Kner, 1858 were recorded to determine their homogeneity between rivers inside a single basin (Araguari and Grande River, upper Paraná River basin) and between separated basins (Amazon and Paraná basins). All fish from the different populations produced sounds with similar acoustic features. Consequently, the populations were not discernible based on individual sound characteristics. This high homogeneity between sounds from different populations indicates their usefulness for conservation projects using passive acoustic monitoring in piranhas. Moreover, it supports the use of acoustic features as complementary key characteristics in taxonomic studies.